2002
DOI: 10.1038/415385b
|View full text |Cite
|
Sign up to set email alerts
|

Amplification by compartmentalization

Abstract: Autocatalysis and chemical amplification are properties of living systems that can lead to increased responsiveness and to self-replication. Here we describe a synthetic system in which a unique form of reagent compartmentalization gives rise to nonlinear kinetics that are subject to the precise size- and shape-selectivity of the host. The reactivity is reminiscent of autocatalytic behaviour, in which there is no direct contact between reagents and products, and our approach offers a general way to impose comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 5 publications
0
56
0
2
Order By: Relevance
“…For example, Rebek's group has elegantly demonstrated that encapsulation of reagents can be utilized to effect chemical amplification in a reaction that takes place outside the capsule. 87,114 The reaction of p-toluic acid 48 or p-ethylbenzoic acid 49 with p-ethylaniline 50 and N,N′-dicyclohexylcarbodiimide (DCC) 51 yields anilides 52 and 53 at almost identical rates, together with N,N′-dicyclohexylurea 54 (DCU) and N-acylurea side-products ( Figure 10). In the presence of a stoichiometric amount of capsule 26-26 (see Figure 4), the reaction rates decreased substantially, and, in addition, p-toluic acid appeared to react much faster than p-ethylbenzoic acid.…”
Section: Noncovalent Systemsmentioning
confidence: 99%
“…For example, Rebek's group has elegantly demonstrated that encapsulation of reagents can be utilized to effect chemical amplification in a reaction that takes place outside the capsule. 87,114 The reaction of p-toluic acid 48 or p-ethylbenzoic acid 49 with p-ethylaniline 50 and N,N′-dicyclohexylcarbodiimide (DCC) 51 yields anilides 52 and 53 at almost identical rates, together with N,N′-dicyclohexylurea 54 (DCU) and N-acylurea side-products ( Figure 10). In the presence of a stoichiometric amount of capsule 26-26 (see Figure 4), the reaction rates decreased substantially, and, in addition, p-toluic acid appeared to react much faster than p-ethylbenzoic acid.…”
Section: Noncovalent Systemsmentioning
confidence: 99%
“…Addition of benzoic acid 15 and aniline 16 to the solution of DCC encapsulated within capsule 8 sets off a reaction cascade (Fig. 3) (27). Trace DCC that is free in solution promotes the formation of an amide bond between the acid and aniline reactants.…”
mentioning
confidence: 99%
“…The relative affinity of the capsule for the guests is DCU ϳ 4a Ͼ DCC. The discrimination of subtle structural differences coupled with the compartmentalization of reagents gives rise to nonlinear kinetics and autocatalytic behavior in reactions involving encapsulated DCC (12).…”
Section: Resultsmentioning
confidence: 99%